PENGGUNAAN METODE PEMBELAJARAN CONCEPT SENTENCE DENGAN MEDIA FLASHCARD DALAM PENINGKATKN KETERAMPILAN MENULIS KARANGAN DI KELAS II SDN 6 PANJER TAHUN AJARAN 2014/2015 - Prasetyaningrum, Nurulia Ika; Prasetyaningrum, Nurulia Ika (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Use of Concept Sentence Learning Method with Flashcard Media to Improve Essay Writing Skills at the Second Grade Students of SDN 6 Panjer in The Academic Year of 2014/2015. This study aims to describe the use of concept sentence with flashcard media in essay writing skills, to improve essay writing skills through concept sentence method with flashcard media. Research subject is second grade SDN 6 Panjer amount of 35 students. The research was conducted in three cycles, each cycles consisting of planning, implementation, observation, and reflection. Data collection techniques using observation, interviews, and testing. Test the validity of data using triangulation techniques. The results showed that the use of concept sentence methods with flashcard media can improve essay writing skills second grade of elementary school. Keyword: Concept Sentence, flashcard, writing skills Abstrak: Penggunaan Metode Concept Sentence dengan Media Flashcard dalam Peningkatan Keterampilan Menulis Karangan di Kelas II SDN 6 Panjer. Penelitian ini bertujuan mendeskripsikan penggunaan metode concept sentence dengan media flashcard dalam peningkatan keterampilan menulis karangan dan meningkatkan keterampilan menulis karangan melalui metode penggunaan metode concept sentence dengan media flashcard, mendeskripsikan. Subjek penelitiannya siswa kelas II SDN 6 Panjer sejumlah 35 siswa. Penelitian dilaksanakan tiga siklus, terdiri atas perencanaan, pelaksanaan, pengamatan, dan refleksi. Teknik pengumpulan data menggunakan observasi, wawancara, dan tes. Uji validitas data menggunakan teknik triangulasi. Hasil menunjukkan penggunaan metode concept sentence dengan media flashcard dapat meningkatkan keterampilan menulis karangan siswa kelas II SD. Kata Kunci: Concept sentence, flashcard, keterampilan menulis